2015
DOI: 10.1155/2015/783468
|View full text |Cite
|
Sign up to set email alerts
|

Late Type 3b Endoleak with an Endurant Endograft

Abstract: Endovascular stent grafting with different commercially available stent graft systems is widely applied for the treatment of abdominal aortic aneurysms with high success rates in the current era. Various types of endoleaks are potential complications of the procedure. They usually occur in the early period. In this report, we present type 3b endoleak occurring 14 months after a successful endovascular abdominal aortic aneurysm repair with a Medtronic Endurant stent graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Thus, the possibility of type I/III was thoroughly reassessed. Despite finding no fabric tear (a cause of type IIIb EL), delayed occurrence of type IIIb EL has been reported in the leg branch region of the main body 5,6) of branching stent grafts, such as the Endurant II ® and Zenith Flex ® (Cook Inc., Indianapolis, IN, USA), which we used in the initial EVAR in our case. Therefore, the possibility of occult type IIIb could not be ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, the possibility of type I/III was thoroughly reassessed. Despite finding no fabric tear (a cause of type IIIb EL), delayed occurrence of type IIIb EL has been reported in the leg branch region of the main body 5,6) of branching stent grafts, such as the Endurant II ® and Zenith Flex ® (Cook Inc., Indianapolis, IN, USA), which we used in the initial EVAR in our case. Therefore, the possibility of occult type IIIb could not be ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that both isolated type II and type IIIB endoleaks lead to late rupture of AAA8, 10; therefore, it was difficult for us to determine the main cause of AAA rupture in our case. Because only the IMA was the causative artery for the type II endoleak in our case, this endoleak was categorized as a type IIA; however, our patient's type II endoleak sustained.…”
Section: Discussionmentioning
confidence: 85%
“…Although it remains unclear whether a type IIIB endoleak can enlarge the aneurysm sac, the cause of the endoleak needs to be recognized when the type cannot be accurately identified 7 . Multiple approaches for the management of type IIIB endoleaks have been proposed 7, 8, 9. For instance, if the anatomic condition is amenable, an endovascular approach is less invasive than explantation of the endograft and graft replacement.…”
Section: Discussionmentioning
confidence: 99%
“…4) In particular, type IIIb endoleak from a fabric tear has been reported even less frequently, with only a few case reports on the Endurant ® and Endurant II ® endografts (Table 1). [5][6][7][8][9] Type IIIb endoleaks were detected at an average of 28 months after EVAR, with three of five cases developing ruptured AAA.…”
Section: Discussionmentioning
confidence: 99%